2004
DOI: 10.1152/ajprenal.00070.2004
|View full text |Cite
|
Sign up to set email alerts
|

CD40-induced transcriptional activation of vascular endothelial growth factor involves a 68-bp region of the promoter containing a CpG island

Abstract: . CD40-induced transcriptional activation of vascular endothelial growth factor involves a 68-bp region of the promoter containing a CpG island. Am J Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…Moreover, while the effect of TRAF1, -2, -3 and -5 was modest, TRAF6 knockdown resulted in a marked induction of basal levels of VEGF expression ( P <0.0001). Also, and consistent with our previously published studies [2,8,21,24], we found that the treatment of EC with sCD40L resulted in a 2-3-fold increase in VEGF transactivation. However, following activation, there was a greater increase in VEGF promoter activity in EC transfected with siRNAs to TRAF2 (approx.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, while the effect of TRAF1, -2, -3 and -5 was modest, TRAF6 knockdown resulted in a marked induction of basal levels of VEGF expression ( P <0.0001). Also, and consistent with our previously published studies [2,8,21,24], we found that the treatment of EC with sCD40L resulted in a 2-3-fold increase in VEGF transactivation. However, following activation, there was a greater increase in VEGF promoter activity in EC transfected with siRNAs to TRAF2 (approx.…”
Section: Resultssupporting
confidence: 93%
“…However, only a few studies have evaluated their expression and function in EC [23,30,31,32], and their role in angiogenesis has not been previously explored. CD40-induced responses in EC are potent to induce VEGF expression, VEGF-dependent EC proliferation in vitro and angiogenesis in vivo [2,3,8,21,24]. Furthermore, CD40-induced angiogenesis is associated with breast cancer growth and progression [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the VEGF promoter was not methylated as analyzed by MSP. The human umbilical vascular endothelial cell, which does not express VEGF and has been reported to involve promoter methylation for VEGF transcriptional regulation, was used as control (25).…”
Section: Methylation Status Of Plgf Promoter In Lung and Colon Carcinmentioning
confidence: 99%
“…Cell suspensions were incubated with primary antibody, washed, and incubated with a secondary FITC-conjugated antibody at 4°C for 30 min as described (14). The stained cells were washed and fixed in 1% paraformaldehyde and analyzed by FACScan (Becton-Dickinson, Oxnard, CA).…”
Section: Flow Cytometrymentioning
confidence: 99%